Potential Role of Quercetin in Polycystic Ovary Syndrome and Its Complications: A Review - Tong Chen; Fan Jia; Yue Yu; Wufan Zhang; Chaoying Wang; Shiqin Zhu; Nana Zhang; Xinmin Liu (Molecules, 2022)
Polycystic ovary syndrome (PCOS) is a common multisystem disease with reproductive, metabolic and psychological abnormalities. It is characterized by a high prevalence rate in women of childbearing age and highly heterogeneous clinical manifestations, which seriously harm women’s physical and mental health. Quercetin (QUR) is a natural compound of flavonoids found in a variety of foods and medicinal plants. It can intervene with the pathologic process of PCOS from multiple targets and channels and has few adverse reactions. It is mentioned in this review that QUR can improve ovulation disorder, relieve Insulin resistance (IR), reduce androgen, regulate lipid metabolism, regulate gut microbiota and improve vascular endothelial function, which is of great significance in the treatment of PCOS.